Bridging Hospitality Education and Community - Cockburn-Wootten, Cheryl; McIntosh, Alison (School of Hospitality & Tourism, Auckland University of Technology, 2020)
The hospitality industry is not immune from the social issues facing our society. There are cases of hospitality initiatives for social change, including philanthropy and social enterprise [1]. In our academic work, the key driver for change is how to overcome silos in order to create engaged, meaningful relationships between hospitality scholars in academia and external community stakeholders [1–3]. We sought to move beyond the traditional confines of academic institutions in order to ‘flip’ mind-sets and practice hospitality for the benefit of wider society. To achieve this vision of hospitality, we needed to work with and within communities. Intervention on long-standing social issues requires wider collaboration – reaching across businesses, third-sector organisations and education institutions. The New Zealand government has been calling on academia to make meaningful relationships that “open up diverse networks of knowledge and resources” for tackling social change [2]. Universities have not always had a good reputation for sustained meaningful engagement with external stakeholders [2]. For instance, typical interactions at universities may include one-way guest lectures or advisory boards who may serve more as a performance of communication for accreditation boards than actual listening and engaging with stakeholders. Dissatisfied with these limiting relationships, “we adopted principles from critical hospitality and dialogue theories to create a long-term space for inclusion, collaboration, and transformational change” [2]. We held a series of community stakeholder meetings using tools, such as Ketso [4, 5], that facilitated co-created conversations with diverse stakeholders – many of whom would not ordinarily have the chance to think through a social problem together. During these meetings, individuals discussed the issue and gained an opportunity to hear, learn and understand each other’s experiences. A recommendation emerged from these meetings [2] for the formation of a network of organisations, charities, individuals and businesses that were interested in tackling social change – called The Network for Community Hospitality (NCH). This recommendation enabled a communication network for diverse stakeholders, ranging from corporates, funders and third sector to individual community organisations to share conversation, resources, knowledge and work on social issues facing our communities. NCH has worked with a variety of stakeholders within communities drawing on different sets of knowledge to tackle social cultural issues related to hospitality, such as social housing, disability and employment, refugee welcome, and poverty. NCH has held ‘Town & Gown’ events to encourage dialogue between stakeholders who may not normally have access to decision-making and financial resources. Invitees to the dinners ranged from businesses to charities and aimed to encourage stakeholders to collectively think through how we can practice and make our communities hospitable. At these dinner events, people with similar interests were strategically placed around the tables. Between dining courses, short three-minute speeches were given by various organisations with a specific call to action for change. Other examples include organisations working with student groups to tackle a particular hospitality issue. Active collaboration with external stakeholders involves student internships/volunteering and students pitching their intervention ideas to the stakeholder. In many cases, after the course key students or student groups will continue either working or (micro-)volunteering with the organisation to help deliver and implement the enterprise or intervention. One of the determinants of success is the mind-set adopted during these processes. The aim is to enact participatory community development approaches that emphasise ‘bottom-up’, co-creation, and dialogue as important tactics for success. Many of the approaches we used were organic, even chaotic at times, inclusive, and always involved friendly conversations over a cuppa and food. Of course, issues can emerge from time to time due to differing understandings around concerns such as timeframes, focus, ownership and commitment. For education, the benefits are that we engage learners in meaningful practices that bridge students’ understanding of theories and real life for a better future. For businesses, it means future hospitality graduates are exposed to real-life issues, well-prepared to manage, able to take leadership and can vision new enterprises and practices for the sector. For society, involving a range of stakeholders to tackle social issues works towards developing inclusive, safe community spaces with a strong sense of civic engagement; in short, a vision for more hospitable communities.